Distributed Data Storage Instead of a Primarily Local Solution? - Severin Kolb; Matthias Schrinner (Journal of the Text Encoding Initiative)
This paper delves into the challenges of creating a comprehensive digital catalog of sources and works for the oeuvre of Franz Liszt, focusing on metadata management. Despite Liszt’s prolific and multifaceted output, existing attempts at systematization have been hindered by the fluidity and complexity of his compositions. The Digital Liszt Catalogue project, funded by the German Research Foundation, aims to address these challenges over a twelve-year period. Rather than adopting a “one tool fits all” approach, the project opts for a distributed data storage solution, leveraging existing repositories like RISM, Zotero, or musiconn.performance alongside local databases. The MerMEId tool is evaluated but found to be lacking in flexibility for Liszt’s catalog in its current form. Instead, the project proposes a “sources first” strategy, prioritizing the cataloging of sources before works. Technical requirements for interoperability and data integration across repositories are outlined, emphasizing the need for a seamless presentation system. The paper concludes by detailing the development of a TYPO3-based presentation system, incorporating advanced features such as graph visualizations to enhance user navigation and comprehension of Liszt’s complex oeuvre.